Neuroscience perspectives on Security: Technology, Detection, and Decision Making - Elena Rusconi (Frontiers Research Topics, 2015)
In security science, efficient operation depends typically on the interaction between technology, human and machine detection and human and machine decision making. A perfect example of this interplay is 'gatekeeping', which is aimed to prevent the passage of people and objects that represent known threats from one end to the other end of an access point. Gatekeeping is most often achieved via visual inspections, mass screening, random sample probing and/or more targeted controls on attempted passages at points of entry. Points of entry may be physical (e.g. national borders) or virtual (e.g. connection log-ons). Who and what are defined as security threats and the resources available to gatekeepers determine the type of checks and technologies that are put in place to ensure appropriate access control. More often than not, the net performance of technology-aided screening and authentication systems ultimately depends on the characteristics of human operators. Assessing cognitive, affective, behavioural, perceptual and brain processes that may affect gatekeepers while undertaking this task is fundamental. On the other hand, assessing the same processes in those individuals who try to breach access to secure systems (e.g. hackers), and try to cheat controls (e.g. smugglers) is equally fundamental and challenging. From a security standpoint it is vital to be able to anticipate, focus on and correctly interpret the signals connected with such attempts to breach access and/or elude controls, in order to be proactive and to enact appropriate responses. Knowing cognitive, behavioral, social and neural constraints that may affect the security enterprise will undoubtedly result in a more effective deployment of existing human and technological resources. Studying how inter-observer variability, human factors and biology may affect the security agenda, and the usability of existing security technologies, is of great economic and policy interest. In addition, brain sciences may suggest the possibility of novel methods of surveillance and intelligence gathering. This is just one example of a typical security issue that may be fruitfully tackled from a neuroscientific and interdisciplinary perspective. The objective of our Research Topic was to document across relevant disciplines some of the most recent developments, ideas, methods and empirical findings that have the potential to expand our knowledge of the human factors involved in the security process. To this end we welcomed empirical contributions using different methodologies such as those applied in human cognitive neuroscience, biometrics and ethology. We also accepted original theoretical contributions, in the form of review articles, perspectives or opinion papers on this topic. The submissions brought together researchers from different backgrounds to discuss topics which have scientific, applicative and social relevance.